Pengaruh Minat Belajar Terhadap Hasil Belajar Passing Sepak Bola Kaki Bagian Dalam - Irsan Kahar; Arsil Pandi; Rasyidah Jalil; Andi Heri Riswanto (Jurnal MensSana, 2022)
The purpose of the study was to determine whether there was an effect of asking to learn on the learning outcomes of soccer passing using the inside of the foot in class VIII MTS Bua students. The research method used descriptive research with the independent variable being interest in learning and the dependent variable being the learning outcomes of passing using the inside of the foot. The population is the entire class VIII MTS Bua, namely 6 groups of 55 students. The sample in this study were 20 students of class VIII MTS Bua. The data analysis technique used the SPSS application program. The results of this study the data there is a value of sig.0,000. The value of sig. is less than 0.05 or the value of 0.000 <0.05, then H1 is accepted and H0 is rejected. The variable of interest in learning has tcount that is 8.177 while ttable = 1.725 so tcount > ttable. The conclusion in this study is that there is a significant effect of learning interest on the learning outcomes of soccer passing using the inside of the foot in class VIII MTS Bua students of 88.8%.